Three-Dimensionally Printed Mini Air Scrubbing Cartridges Based on Nano-Graphite for Air Pollution Monitoring - Emiliano Zampetti; Mattia Ammiraglia; Marco Conti; Cassandra Montiroli; Paolo Papa; Daniele Bianconi; Antonella Macagnano (Sensors)
Ecosystems and environments are impacted by atmospheric pollution, which has significant effects on human health and climate. For these reasons, devices for developing portable and low-cost monitoring systems are required to assess human exposure during daily life. In the last decade, the advancements of 3D printing technology have pushed researchers to exploit, in different fields of applications, the advantages offered, such as rapid prototyping and low-cost replication of complex sample treatment devices. In this work, we present the fabrication and testing of 3D printed cartridges based on both commercial photopolymer and a modified version with the intrusion of nano graphite. The air scrubbing performances towards some volatile organic compounds have been investigated, inserting the cartridges into a low-cost monitoring system using a photoionization sensor. In particular, the cartridges were tested in the presence of concentrations of ethanol, benzene, and toluene to evaluate the abatement percentage with and without their use. Although the results have shown that all cartridges abated ethanol and toluene, the abatement of benzene increased 20 times in the case of cartridges based on modified resin with nano graphite. These results could enable their employment to reduce the concentration of interfering compounds in low-cost monitoring systems.